2018
DOI: 10.3892/ol.2018.9187
|View full text |Cite
|
Sign up to set email alerts
|

H19 contributes to poor clinical features in NSCLC patients and leads to enhanced invasion in A549 cells through regulating miRNA‑203‑mediated epithelial‑mesenchymal transition

Abstract: Recent studies have demonstrated that the overexpression of H19 may contribute towards development of tumorigenesis in various types of cancer. To investigate the role of H19 in the development of non-small cell lung cancer (NSCLC), 76 NSCLC tissues samples and their adjacent normal tissue samples were collected. Expression level of H19, and its association with clinicopathological features and overall survival was analyzed. It was found that compared with normal adjacent tissues, H19 expression was elevated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Studies have revealed that the expression of H19 is significantly increased in LC tissues when compared with that in adjacent tissues [40,66]. H19 overexpression is associated with carcinogenesis from early stages to metastasis, reduced disease-free survival (DFS) time, and poor prognosis in LC [4,41,46,67].…”
Section: Lncrnas In Lung Cancer (Lc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed that the expression of H19 is significantly increased in LC tissues when compared with that in adjacent tissues [40,66]. H19 overexpression is associated with carcinogenesis from early stages to metastasis, reduced disease-free survival (DFS) time, and poor prognosis in LC [4,41,46,67].…”
Section: Lncrnas In Lung Cancer (Lc)mentioning
confidence: 99%
“…Zhao et al indicated that the overexpression of H19 sponged and inhibited miR-200a function to upregulate zinc finger E-box binding homeobox 1 (ZEB1) and zinc finger E-box binding homeobox 2 (ZEB2), thereby promoting proliferation, migration, invasion, and EMT in LC [40]. It has been demonstrated that upregulation of H19 can induce cell proliferation, invasion, and EMT occurrence by acting as an miRNA sponge and regulating miRNA-203-mediated EMT [66]. Additionally, H19 can induce cell proliferation by promoting the expression of pro-oncogene lin-28 homolog B (LIN28B) via the inhibition of miR-196b expression in A549 and H1299 LC cell lines [71].…”
Section: Lncrnas In Lung Cancer (Lc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lung-cancer treatment is promising if the disease is detected at its early stage, and less beneficial at advanced stage, though a relatively high risk of recurrence occurs even after exposure to available potent treatment (3). NSCLC migration and invasion contribute to poor treatment outcome and lung-cancer mortality (4). NSCLC cells aggressively proliferate and invade adjacent tissues, cross the basement membrane and migrate to establish colonies in distant organs of the body via either the vascular system or the lymphatic system (5).…”
Section: Introductionmentioning
confidence: 99%
“…Rani et al (2016) proved that lncRNA-LnND was significantly downregulated in neuroblastoma by participating in miRNA-mediated regulation of Notch signaling. Ge et al (2018) declared that high-H19 expression greatly promoted cells proliferation, invasion, and contributed to poor clinical features in patients with nonsmall cell lung cancer through regulating miRNA-203-mediated epithelial-mesenchymal transition. The result of bioinformatic analysis showed that lncRNA-CYTOR mainly located in cytoplasm in a variety of cancer cell lines 5 (Fig.…”
mentioning
confidence: 99%